LRP5 BIALLELIC MUTATIONS CAUSE A HIGHER INCIDENCE OF SEVERE PHENOTYPE COMPARED WITH LRP5 MONOALLELIC MUTATION. Issue 10 (October 2022) - Chen, Chunli; Zhang, Xiang; Peng, Xiaoyan; Hu, Feng; Cheng, Yizhe; Zhao, Peiquan
Abstract : Supplemental Digital Content is Available in the Text. This retrospective study is to analyze the clinical features of LRP5 gene mutation-related familial exudative vitreoretinopathy and explore the potential correlation between the phenotype and genotype on LRP5 gene. Abstract : Purpose: To analyze the clinical features of LRP5 gene mutation-related familial exudative vitreoretinopathy and explore the potential phenotype–genotype correlation on LRP5 gene. Methods: Eighty-seven familial exudative vitreoretinopathy (FEVR) families with LRP5 mutations were selected from 722 FEVR patients, which were divided into 2 groups, including 22 autosomal-recessive FEVR (ar-FEVR) families and 65 autosomal-dominant FEVR (ad-FEVR) families. Clinical and genetic data were retrospectively analyzed. The potential phenotype–genotype correlation was explored from the mutation type and inheritance pattern. Results: No significant difference between the LRP5 null mutation subgroup and the LRP5 missense mutation subgroup was observed in the proportion of FEVR stage and the ratio of ocular involvement. Instead, a significant difference between the LRP5 ar-FEVR subgroup and the LRP5 ad-FEVR subgroup was observed in the proportion of FEVR stage and the ratio of binocularly severe phenotype. The probands with LRP5 gene recessive mutation showed a higher incidence of severe phenotype. Moreover, the ratio of binocularly severe patients in ar-FEVR was nearly 3.5 times higher than that in ad-FEVR. Conclusion: The severity of phenotype was more likely to be related to the synergistic effect of the variants.